'Scheduled Tribe Dalit' and the Recognition of Tribal Casteism. Issue 1 (June 2020) - Christopher, Stephen
While the term 'tribalism' in the West draws from outmoded anthropological theory to describe the hardening of partisan group boundaries, in Himachal Pradesh it describes the contested recognition of caste heterogeneity within Scheduled Tribes (ST). Based on 15 months of fieldwork among Gaddis, this article seeks to understand the intersectionality of low-caste groups embedded within tribal formations, partially assimilated, unevenly accepted and without legal protections afforded to other marginalised communities. I argue that recognising tribal casteism is the first step to theorise tribal multiculturalism and the ever-contested broadening of communal boundaries. By tracking the discourse of 'Scheduled Tribe Dalit' (STD) in the Western Himalayas, this article analyses the looping effect between emic belonging and the role of state ethnology in incentivising difference.